Relevansi Pilar Moderasi Beragama Quraish Shihab pada Upacara Rambu Solo’ Toraja di Kelurahan Ratte Buttu, Tana Toraja - Muhammad Ilham Ramadhan; Anwar Fuadi; Bayani Dahlan; Nuryadin Nuryadin; Akhmad Gifari (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2024)
Indonesia, a country with a rich cultural tapestry, is not immune to the challenges posed by cultural conflicts. These conflicts are often rooted in historical tensions between tribes and religions, which continue to manifest in the form of respect, mutual respect, and the acceptance of differences. A solution is required to cultivate an attitude of religious moderation as a way of life in order to maintain harmony by upholding the pillars of justice, balance and tolerance. These pillars were initiated by Quriash Shihab using qualitative methods. It was found that the pillar of religious moderation has relevance to the traditions of the Tana Toraja people in the Rambu Solo event. The funeral tradition of Rambu Solo teaches about unity and social balance between people in ceremonial traditions, justice between followers of one religion and tolerance between adherents of Christianity as the majority and Islam as a minority religion.